In re obscura versantes. The complex hagiography of the martyrs of Amiternum and new ways of its interpretation - Capannolo, Luca (Saeculum Christianum. Pismo Historyczne, 2021)
The biography of the eighty-three Martyrs of Amiternum has always been a source of controversy among scholars of hagiography. Scant data and lack of research on the topic have made the complex hagiography of the Martyrs of Amiternum even more difficult to understand. The aim of this paper is not to solve the issue, but only to collect the available hagiographic material and use the few reliable fact about the lives of the Martyrs of Amiternum to offer new perspectives for further hagiographic study.